Gestão da qualidade e do trabalho imaterial: uma análise a partir da dinâmica informacional - Jorge, Vanessa de Arruda (2012)
The focus of this research is to analyze the information on quality management based on ISO, in the context of transformations of the forms of production and work from post-Fordism. It explres the argument of the two perspectives in the analysis of information and quality management standard